Within‐couple configuration of gender‐related attitudes and its association with marital satisfaction in Chinese marriage: A dyadic, pattern‐analytic approach. Issue 6 (6th March 2019) - Cao, Hongjian; Li, Xiaomin; Chi, Peilian; Du, Hongfei; Wu, Qinglu; Liang, Yue; Zhou, Nan; Fine, Mark A.
Abstract: Objective: This study seeks to understand the ways in which spouses' gender‐related attitudes are configured within couples and how such configurations are linked to marital satisfaction in Chinese marriage. Method: Latent profile analysis was conducted using dyadic data from a nationwide large sample of Chinese couples from the China Family Panel Studies ( N = 7, 257 couples; M years of marriage = 28.36, SD = 12.84; M age for wives = 52.38, SD = 12.63; M age for husbands = 50.51, SD = 12.37). Results: Four profile groups were identified: the "modern female and traditional male" group (MFTM); the "traditional female and modern male" group; the "child‐oriented" group; and the "traditional female and traditional male" group. Husbands' and wives' marital satisfaction varied across groups in different patterns (yet all relevant effect sizes were modest). In general, husbands in the congruent group reported higher satisfaction than did those in the incongruent groups, whereas wives in the "MFTM" group reported lower satisfaction than did those in the other groups. Conclusions: Such findings shed light on the understudied heterogeneity that inherently exists in the within‐couple patterning of gender‐related attitudes and its implications for marital well‐being in a Chinese cultural context.